The agathological horizon of Tischner’s philosophy of education as a horizon of “the promised land” and/or “land of denial” - Jaroslaw Gara (Studia z Teorii Wychowania)
Józef Tischner’s philosophy of education reflects his assumed philosophy of man, which programmatically refers to the heuristic potential of “thinking from the depth of a metaphor”. Tischner’s agathology is based on the assumption that human life is governed by the “logos of good and evil”. Therefore, human existence takes the form of “dramatic existence”, and man himself appears as an “axiological being”, which experiences values and adopts specific attitudes towards them. In this meaning, one of the basic tasks of educators is conveying the “fundamental hope”, according to which discovering one’s life calling is possible. Therefore, education is a guide to authentic and original forms of the existential realization of good. The world as “the scene of human drama” embraces the hope that this world will become man’s “promised land” and the threat that it will be for him a “denied land”. In this context, human life plays out as the act of rooting or uprooting in the specific sphere of human experience, considered both physically and symbolically, including “home”, “workshop”, “temple”, or “cemetery”. Although in his concept of philosophy of drama, Tischner does not refer directly to the issue of education in the perspectives of the “promised land” and “land of denial” addressed here, there are many indications that these issues supplement his statements that directly define his concept of education.